Constructing Meaning in Computer-Mediated Communication: A Speech Act Perspective - Angela Shakila Aurel Pane; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study investigates how speech acts function in online communication, particularly in the absence of non-verbal cues such as tone of voice, gestures, and facial expressions. Adopting the framework of speech act theory by Austin and Searle, the research explores how users perform communicative actions like requesting, apologizing, and asserting using only text and platform-specific tools. Employing a qualitative approach, this research analyzes messages from online platforms to identify types of speech acts and strategies users apply to ensure their intent is understood. The findings reveal that users adapt language and utilize emojis, timing, punctuation, and politeness strategies to construct meaning and maintain interactional harmony. The study concludes that pragmatic competence and contextual awareness are critical to effective digital interaction. The implications of these findings highlight the importance of integrating digital pragmatics into language education, user training, and platform design to enhance the quality of online communication in various social and professional settings.